COMPLEXITY IN LEADERSHIP: TRANSLATING THEORY INTO PRACTICE IN AUSTRALIA'S NDIS REFORM - Putra, Fajar Surya (Scientia Integritas Utama, 2023)
In an era of increasing global complexity, policy leaders must navigate multifaceted challenges such as the COVID-19 pandemic, gender equality, and climate change, which require interdisciplinary approaches. Complexity theory offers a valuable framework to understand the interconnectedness among policy actors and the unpredictable nature of policymaking. This paper examines the practical application of complexity theory through the case study of Australia’s National Disability Insurance Scheme (NDIS). It highlights the crucial role of policy leaders in managing uncertainty, unintended consequences, and interdependent relationships. By exploring the dynamics of political leadership within the NDIS system, this study underscores the need for inclusive cooperation, stakeholder engagement, and adaptive governance. It also addresses the unintended consequences of policy implementation, such as service disparities and funding uncertainties. Finally, the paper provides insights into how complexity theory can inform contemporary academic discourse and policymaking strategies, advocating for a shift from linear solutions to more adaptive and iterative policy approaches.